Laparoscopic splenectomy and azygoportal disconnection combining with pre- and postoperative endoscopic intervention - A sandwich-style sequential therapy for portal hypertensive bleeding: A retrospective cohort study - Ba, Dou-Sheng (Turk J Gastroenterol, 2018)
BACKGROUND/AIMS: In patients who survive the first esophageal variceal bleeding (EVB) resulting from portal hypertension, the probability of fatal esophageal variceal re-bleeding (EVR) is high. We have developed a sandwich-style sequential therapy combining laparoscopic splenectomy and azygoportal disconnection (LSD) with preoperative and postoperative endoscopic intervention (LSDE). The aim of the present study was to investigate whether LSDE is safe and effective and to evaluate whether the postoperative EVR rate for LSDE was lower than that for LSD without periodical postoperative endoscopic intervention (NLSDE). MATERIALS AND METHODS: We retrospectively investigated the outcomes of 226 patients with cirrhosis with EVB and secondary hypersplenism who all received preoperative endoscopic variceal ligation (EVL) to manage emergency EVB then underwent NLSDE (n=106) or LSDE (n=120) between February 2012 and April 2016. The perioperative and follow-up variables of the two groups were evaluated. RESULTS: Between the two groups, there were no differences in number of blood transfusions, intraoperative blood loss, postoperative complications, and hospital stay. LSDE showed shorter operation time (p=0.001) and lower EVR rates during the periods ranging from 1 to 12 months, 4 to 6 months, 4 to 12 months, and 7 to 12 months (all p<0.05) than NLSDE. Dynamic changes in the diameter of the esophageal varices and the rates of EVL in the LSDE group both decreased gradually and significantly over the 12-month follow-up period (all p<0.0001). CONCLUSION: Laparoscopic splenectomy and azygoportal disconnection with periodical postoperative endoscopy is safe and effective for reducing the EVR rate in cirrhotic portal hypertension.